2020
DOI: 10.1016/j.drugalcdep.2020.107949
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional surveys of financial harm associated with others’ drinking in 15 countries: Unequal effects on women?

Abstract: Introduction and aims: That physical, emotional and social problems occur not only to drinkers, but also to others they connect with, is increasingly acknowledged. Financial harms from others' drinking have been seldom studied at the population level, particularly in low-and middleincome countries. Whether financial harm and costs from others' drinking inequitably affect women is little known. The study's aim is to compare estimates and correlates of alcohol's financial harm to others than the drinker in 15 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Statistics on drinking and alcohol-related harm show that men in LMIC are twice as likely to be drinkers, drink three times the amount that women do and are more likely to drink in a heavy episodic way if they drink [6]. This places many women in LMIC and elsewhere at increased risk of a range of harms related to the drinking of men, including physical and sexual violence, having to leave home, financial difficulties and responsibility for caring for drinkers in their families [7][8][9][10]. The World Health Organization (WHO) Multi-Country Study on Women's Health and Domestic Violence in 10 countries found that the risk of experiencing IPV increased when women and/ or their partners had attitudes supportive of violence and problems with alcohol [11].…”
Section: Introductionmentioning
confidence: 99%
“…Statistics on drinking and alcohol-related harm show that men in LMIC are twice as likely to be drinkers, drink three times the amount that women do and are more likely to drink in a heavy episodic way if they drink [6]. This places many women in LMIC and elsewhere at increased risk of a range of harms related to the drinking of men, including physical and sexual violence, having to leave home, financial difficulties and responsibility for caring for drinkers in their families [7][8][9][10]. The World Health Organization (WHO) Multi-Country Study on Women's Health and Domestic Violence in 10 countries found that the risk of experiencing IPV increased when women and/ or their partners had attitudes supportive of violence and problems with alcohol [11].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, this could lead to direct effects upon women and children's health, safety, finances and wellbeing (Leonard & Quigley, 2017). There is plenty of evidence that alcohol causes a range of harms to families and children (Laslett, Jiang, et al, 2020;Laslett, Mojica-Perez, et al, 2021; and this study highlights how reductions in drinking may be associated with more positive outcomes. Programs that reduce HED among men may well mean men have more time to spend with their children.…”
Section: Discussionmentioning
confidence: 82%
“…One in five US adults report having experienced harms in the previous year because of someone else's drinking [1]. Such harms involve social, mental health and medical difficulties [2][3][4]. The Al-Anon Family Groups program (known simply as 'Al-Anon') helps concerned others (COs; that is, friends and family members concerned about another's drinking) who may be experiencing such harms.…”
Section: Introductionmentioning
confidence: 99%